RNA sequence variants in live poliovirus vaccine and their relation to neurovirulence. - Chumakov, K M (1992)
Mutant analysis by polymerase chain reaction and restriction enzyme cleavage (MAPREC) was used to study sequence heterogeneity and stability in attenuated poliovirus type 3 at positions in which the vaccine virus differs from its wild-type progenitor. Of seven genomic positions tested, only two (positions 472 and 2493) show nucleotide heterogeneity. Propagation of the vaccine virus in cell cultures leads to rapid selection of virus with reversions at these two positions of the genome. The relative abundance of reversions at position 472 correlates with the results of monkey neurovirulence tests, while the mutation at position 2493 is not directly associated with neurovirulence of the virus in monkeys. Instead, the abundance of mutations at the latter position correlates with the source of the seed virus and its passage level. These results further indicate that MAPREC at position 472 can be used to assess the quality of poliovirus type 3 vaccine.